2016
DOI: 10.1371/journal.pgen.1005853
|View full text |Cite
|
Sign up to set email alerts
|

Common and Low Frequency Variants in MERTK Are Independently Associated with Multiple Sclerosis Susceptibility with Discordant Association Dependent upon HLA-DRB1*15:01 Status

Abstract: Multiple Sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system. The risk of developing MS is strongly influenced by genetic predisposition, and over 100 loci have been established as associated with susceptibility. However, the biologically relevant variants underlying disease risk have not been defined for the vast majority of these loci, limiting the power of these genetic studies to define new avenues of research for the development of MS therapeutics. It is therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 54 publications
(64 reference statements)
0
35
0
1
Order By: Relevance
“…62 Unsurprisingly, defects in efferocytic receptors and signaling molecules are associated with the onset of autoimmune disorders including rheumatoid arthritis, multiple sclerosis and systemic lupus erythematosus, 11, 63, 64 and with chronic inflammatory conditions such as atherosclerosis. 13, 15, 65 However, this regulation must be more nuanced than simply sorting all degraded apoptotic cells away from the MHC class II loading compartment, as apoptotic cells can harbor pathogens and act as vehicles for pathogen dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…62 Unsurprisingly, defects in efferocytic receptors and signaling molecules are associated with the onset of autoimmune disorders including rheumatoid arthritis, multiple sclerosis and systemic lupus erythematosus, 11, 63, 64 and with chronic inflammatory conditions such as atherosclerosis. 13, 15, 65 However, this regulation must be more nuanced than simply sorting all degraded apoptotic cells away from the MHC class II loading compartment, as apoptotic cells can harbor pathogens and act as vehicles for pathogen dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the same group reported that one specific variant of MerTK gene, so called rs7422195, has discordant association to MS according to HLA (human leukocyte antigen)-DRB1*15:01 status, being protective in DR15 homozygosity and favouring the disease in the absence of DR15. The minor allele of rs7422195 is also associated to an increased gene and protein expression of MerTK in monocytes and CD4 + cells [105]. Whether this subset of cells was formed by T cells or contaminated by monocytes expressing CD4 is not yet known.…”
Section: Evidence About the Role Of The Gas6/tam System In Multiplmentioning
confidence: 99%
“…GWAS has identified several SNPs in the MERTK gene as independently associated with the risk of developing MS (12, 25). Fine-mapping of the MERTK locus identifies a risk variant that operates in trans with the HLA-DRB1 locus and is associated with higher expression of MerTK in MS patient monocytes (13). This particular SNP (rs7422195) displays discordant association depending on the individual’s HLA-DRB1*15:01 status, conferring increased risk, but converting to a protective effect on an HLA-DRB1*15:01 homozygous background.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have explained much of MS heritability. Single nucleotide polymorphisms (SNPs) in CYP24A1 and CYP27B1 , which tightly regulate the intracellular levels of calcitriol have been associated with an increased risk of MS (11) (12, 13).…”
Section: Introductionmentioning
confidence: 99%